Effect of enzymatic pro-oxidant and antioxidant systems on bovine oocyte in vitro maturation - Morado, Sergio Adrián (2021)
The role of reactive oxygen species (ROS) during oocyte in vitro maturation (IVM) is still controversial. Although an increase in ROS production may cause deleterious effects in cells, these reactive species may also act as signaling molecules influencing different cell functions. The aim of this study was to examine the effect of varying endogenous ROS levels during IVM on the process of bovine oocyte maturation. To do so, different enzymatic antioxidant (catalase, or superoxide dismutase + catalase, or diphenyl iodonium) or pro-oxidant systems (xanthine + xanthine oxidase, or xanthine + xanthine oxidase + catalase) were added to the culture medium. ROS levels were determined by 2′,7′-dichlorodihydrofluorescein diacetate stain, nuclear maturation was evaluated by the presence of the metaphase II chromosome configuration at 22h of IVM and cleavage rate was recorded 48hs post- in vitro fertilization. ROS levels were only significantly increased (P<0.05) by the O2.- generating system (xanthine + xanthine oxidase + catalase), but meiotic maturation rates were significantly lower (P<0.05) in all the evaluated systems compared with the control, except for the diphenyl iodonium group. However, this last group presented a significantly lower (P<0.05) cleavage rate in comparison to the control group. These results indicate that ROS would play an essential role during oocyte maturation, since its increase or decrease beyond a physiological level significantly reduced nuclear or cytoplasmic maturation rates in bovine oocytes.